Reproductive performance and plasma profile of alkaline phosphatase, progesterone and thyroid hormones in postpartum fertile and infertile Surti buffaloes - KHASATIYA, C T; DHAMI, A J; SARVAIYA, N P; KHARADI, V B; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
The reproductive performance, AKP and plasma endocrine profile was studied in fertile (n=l 2) and infertile (n=l l) Surti buffaloes at weekly interval from the day of calving till 15 weeks postpartum. The period for initiation of postpartum ovarian follicular activity, first oestrus postpartum, days open and calving interval were significantly shorter (P < 0.01) in fertile group of buffaloes than the infertile ones. The plasmaAKP activity was consistently higher in fertile than the infertile buffaloes, and it showed a gradual increasing trend from calving till 151h week postpartum, but without significant weekly variation in both the groups. The mean P4 levels varied significantly between weeks postpartum only in fertile group1 The values of 0.81 ± 0.18 ng/ml on the day of calving dropped to base line and remained low until 8 weeks postpartum and then showed increasing trend as the weeks proceed to reach the highest value (P < 0.01) of2.77 ± 0.27 ng/ml at 151h week postpartum, while in the infertile group the levels fluctuated non-significantly and the values were higher at week 61h, 9th and 13 th with fall in-between, suggesting anoestrus/suboestrus condition, repeat cycles or early embryonic death in some animals. The levels of both T1 and T4 were highest on the day of calving, dropped by 3-4 weeks postpartum and remained low thereafter. Further. the levels ofT4 were apparently higher in infertile than the fertile group at all intervals with significant difference in the overall means. The P 4 levels had significant correlations with T1 (0. 75) and with resumption of follicular activity, first heat postpartum, days open and calving interval (-0.58, -0.72, -0.87, -0.85) in fertile group. The levels ofT1 showed significant negative correlations with FOPP, days open and calving interval (-0.55, -0.85, -0.81) only in fertile group, while T4 had negative correlation with services per conception (-0.74) in fertile group. AKP had no significant correlation with any of the reproductive or hormonal traits.